Analysis of the Implementation of Internal Control in the Presentation of Financial Statements Based on SAK ETAP at KSP Kopdit Tuke Jung - Evivivania, Emilia; Herdi, Henrikus; Aurelia, Pipiet Niken; Lewar, Maria Viviana Nurak (Neo Journal of economy and social humanities, 2025)
This study aims to determine the application of internal control in the presentation of financial statements based on SAK ETAP at KSP Kopdit Tuke Jung. This type of research uses a qualitative descriptive approach. Data analysis is carried out by organizing data, describing it into units, synthesizing, organizing it into patterns, choosing which ones are important and what will be learned, and making conclusions that can be told to others—the application of internal control in the presentation of financial statements based on SAK ETAP on KSP. Kopdit Tuke Jung has not been implemented properly. Analysis of the implementation of internal control in the presentation of financial statements based on SAK ETAP conducted on KSP. Kopdit Tuke Jung related to the control environment, risk interpretation, control activities, information and communication, and monitoring are quite effective. However, there are still some weaknesses, especially in the aspect of mastering the technical mastery of financial reporting according to SAK ETAP.